Happiness at the End of Life: A Qualitative Study. (March 2021) - O'Callaghan, Anne; Bickford, Ben; Rea, Conor; Fernando, Antonio; Malpas, Phillipa
Background: Happiness is a core ingredient of health and well-being, yet relatively little is known about what happiness means for individuals near the end of life, and whether perceptions of happiness change as individuals approach the end of their lives. Aim: The aim of this study was to explore, through interviews, how individuals experiencing hospice care understood and conceptualized happiness. Design: Qualitative interviews with hospice patients were analyzed thematically. Setting/Participants: Adult patients (n = 20) in a New Zealand hospice who were receiving palliative care and who could give their informed consent were invited by hospice nurse coordinators to an interview. Results: Four themes emerged from analysis of the transcribed interviews. Participants defined happiness most frequently and in most depth in relation to connection with others. They identified being in the present moment, particularly in relation to nature, and that happiness had become less associated with money, status, or possessions. They had an attitude of determination to focus on what mattered now. Conclusion: Patients receiving palliative care were generally happy with their lives, appreciated the simpler aspects of life away from the material. There was a common exhortation to young people to avoid focusing too much on acquisition and the internet and to prioritize instead social connection and engagement with the natural world.